Eco-print on Recycle Paper and Fabric as Main Products of Business Development Program of Intellectual Property Campus of Universitas Sumatera Utara : Eco-print on Recycle Paper and Fabric - Nuryawan, Arif (Talenta Publisher Universitas Sumatera Utara, 2020)
The purpose of this work is to provide seminar needs (seminar kit) as compliments of seminar or symposium held by university including Universitas Sumatera Utara (USU). Method of this activity included launching of our main products, namely eco-print both on paper and on fabric. In this work, eco-print products on recycle papers was used as exclusive block-note covers while eco-print products on fabric were used as tote-bag materials. There were two advantages of using these products, firstly: they were made of natural ingredients without chemical synthetic materials; and secondly the products were designed specifically; one product was not similar with the others. This activity involved two partners, namely a recycle-paper producer and a tailor who make tote-bag. Result on progress of this activity was an order for seminar kit through exhibition. During the evaluation of this project it was found that Nauli Apik USU, as a seminar kit’s producer, still depends on workers whom working manually and having individual skill. In the future, management of production should be improved.